Short-Term Persistence in Mutual Funds Performance: Evidence from India - Sanjay Sehgal; Manoj Jhanwar (Journal of Accounting, Business and Management (JABM), 2008)
In this paper, we examine if there is any short-term persistence in mutual funds performance in the Indian context. We find no evidence that confirms persistence using monthly data. Using daily data, we observe that for fund schemes sorted on prior period four-factor abnormal returns, the winners portfolio does provide gross abnormal returns of 10% per annum on post-formation basis. The economic feasibility of zero-investment trading strategies that involve buying past winners and selling past losers is however in doubt. This is owing to the fact that these strategies generate low gross returns and that the winners portfolios involve higher investment costs than losers portfolios, thus eliminating a major portion of extra-normal returns. Our empirical findings are consistent with the efficient market hypothesis and have implications for hedge funds and other managed portfolios who rely on innovative investment styles, including the "fund of funds" trading strategies that implicity assume short-term persistence